The Effect of Betulin Diphosphate in Wound Dressings of Bacterial Cellulose-ZnO NPs on Platelet Aggregation and the Activity of Oxidoreductases Regulated by NAD(P)+/NAD(P)H-Balance in Burns on Rats - Nina Melnikova (Molecules, 2021)
The inhibition of platelet aggregation, and the activity of oxidoreductases and microhemocirculation in a burn wound on the treatment of burns with wound dressings based on bacterial nanocellulose (BC)-zinc oxide nanoparticles (ZnO NPs)-betulin diphosphate (BDP) were studied. The control of the treatment by BC-ZnO NPs-BDP on burned rats by the noninvasive DLF method showed an increase in perfusion and the respiratory component in wavelet spectra, characterizing an improvement in oxygen saturation in the wound. The study on the volunteers’ blood found the inhibition of ADP-induced platelet aggregation by 30–90%. Disaggregation depends on the dose under the action of the ionized form of BDP and ZnO NPs-BDP in a phosphate buffer; it was reversible and had two waves. It was shown on rats that the specific activity of LDHreverse and LDHdirect (control-intact animals) on day 21 of treatment increased by 11–38% and 23%, respectively. The LDHreverse/LDHdirect ratio increased at BC-ZnO NPs-BDP treatment, which characterizes efficient NAD+ regeneration. AlDH activity increased significantly in the first 10 days by 70–170%, reflecting the effectiveness of the enzyme and NAD+ in utilizing toxic aldehydes at this stage of burn disease. The activities of GR and G6PDH using NADP(H) were increased with BC-ZnO NPs-BDP treatment.